Sequential detection/isolation of abrupt changes. Issue 3 (2nd July 2016) - Nikiforov, Igor V.
ABSTRACT: The quickest multidecision change detection/isolation problem is the generalization of the quickest changepoint detection problem to the case of M post-change hypotheses. It is necessary to detect the change in distribution as soon as possible and to indicate which hypothesis is true after a change occurs. Both the rate of false alarms and the misidentification (false isolation) rate should be controlled by given levels. Several detection/isolation procedures that asymptotically minimize the tradeoff between the expected detection delay and the false alarm/false isolation rates in the worst-case scenario are discussed.